Study the Behavior of Activity and Express for Enzymes - Antesar Rheem Obead; Anmar Hameed Bloh; Haider Rasol Abbass Alwahami (Institute of Medico-legal Publications Pvt Ltd, 2021)
Enzymes are be defined as soluble, colloidal, organic catalysts which are produced by living cells.Enzymes are biologic catalysts to accelerate the rate of biochemical reactions.in this study Quantification of the Enzyme Activity, Where: E = enzyme concentration; S = substrateconcentration; ES = enzyme-substrate complex concentration; k1, k3= 1st order reaction rate constants(t-1); P = product concentration; k2= 2nd reaction rate constant (M-1.t-1).At first, it must be stressed thatthe formation of ES (enzyme-substrate complex) is an obligatory step to any type of enzyme-catalyzedreaction. The ES, depending on the reaction conditions, can form the product (forward reaction) ornot (reward reaction). The immobilization technique allowed a more frequent use of biomaterials inindustry, therapeutics (confection of subcutaneous capsules for controlled delivering of hormones), andlab analysis (automatic dosing equipments, enzyme electrode, biosensors and enzyme immunoassays).In industry, the use of glucose isomerase for the conversion of glucose into fructose (high fructosecorn syrup), the aminoacylase for the separation of racemic mixture of amino acids, microbial lipase intriglyceride hydrolysis, and the lactase for removing lactose from milk and/or whey are stressed.